KONTRIBUSI ‘ALI AL-MADINI TERHADAP RIJAL AL-HADITHDALAM KITAB IMAM AL-BUKHARI - Alwi Shobri; Babun Najib (AL-BAYAN INSTITUTE, 2025)
‘Ali al-Madini (161-234 H) is known as one of the teachers of Imam al-Bukhari, who is widely regarded for making significant contributions to the understanding of al-Bukhari, particularly in the aspect of rijal al-hadith. al-Madini’s participation in influencing the character and methodology of compiling al-Bukhari’s books reflects a profound role in the realm of rijal al-hadith that, to this day, has not been comprehensively addressed in studies. Therefore, the objective of this study is to track the contributions ‘Ali al-Madini in the context of rijal al-hadith as an attempt to explore the participation of al-Madini’s thought in the book of Imam al-Bukhari. The analytical approach utilized in this study is substantive analysis technique (content analysis) through the bibliographic approach proposed by Ibn al-Nadim, by identifying and analyzing texts and documents relevant to the topic under discussion. Substantially, various aspects are examined in this study, starting from the depiction of the life story of ‘Ali al-Madini, the critical reasoning of al-Madini in rijal al-hadith, proceeded by assessing the credibility of al-Madini from the viewpoint of Imam al-Bukhari, and concluding with an analysis contributions of ‘Ali al-Madini in the aspect of rijal al-hadith in two books of Imam al-Bukhari: al-Jami’ al-Sahih and al-Tarikh al-Kabir. The results of this research reveal ‘Ali al-Madini’s involvement to the field of rijal al-hadith through the methodology of compiling two books of Imam al-Bukhari: al-Jami’ al-Sahih and al-Tarikh al-Kabir. al-Bukhari also frequently refers to the viewpoints of al-Madini and references the hadith that al-Madini strengthens in the evaluation of their narrators